Interaction between heparan sulphate chains II. Structural characterization of iduronate- and glucuronate-containing sequences in aggregating chains - Fransson, L.-Å; Havsmark, B.; Nieduszynski, I.A.; Huckerby, T.N. (Biochimica et biophysica acta, 1980)
A heparan sulphate fraction (uronic acid composition: 20% sulphated iduronate, 15% iduronate and 65% glucuronate of total uronate) was separated into aggregating and non-aggregating chains by gel chromatography. 13C-NMR analyses revealed that non-aggregating chains had a higher degree of sulphation than did aggregating chains. In aggregating chains, there was more N-acetyl-glucosamine than N-sulphamidoglucosamine; the extent of C-6 sulphation of the latter moiety was low and most of the iduronate residues were non-sulphated. In non-aggregating chains, the N-acetyl-to- N-sulphate ratio was approx. 2 : 1, the N-sulphated glucosamines were also largely C-6 sulphated and the sulphated iduronates were concentrated to these species. Both preparations were subjected to deaminative cleavage which produces fragments like uronate-( N-acetylglucosamine-uronate) n -anhydromannose. Tetrasaccharides ( n = 1) were further fractionated into non-, mono-, di- and trisulphated species by ion-exchange chromatography. The tetrasaccharides have the general carbohydrate structure uronate- N-acetylglucosamine-glucuronate-anhydromannose. Non-reducing terminal glucuronate was removed by β-glucuronidase. The results showed that saccharides containing glucuronate in both positions were more prevalent in the products of aggregating chains. The β-glucuronidase-resistant saccharides (carrying either sulphated or non-sulphated iduronate in non-reducing terminal position) were oxidised with periodate under conditions where non-sulphated residues are degraded, whereas sulphated residues are resistant. Mono-sulphated and di-sulphated tetrasaccharides from aggregating chains were extensively degraded indicating that iduronate- N-acetylglucosamine-glucuronate-anhydromannose was the major sequence. In saccharides from non-aggregating chains iduronate was frequently sulphated. The results of this and previous investigations (Fransson, L.-Å., Nieduszynski, I.A. and Sheehan, J.K. (1980) Biochim. Biophys. Acta 630, 287–300) indicate that an alternating arrangement of iduronate and glucuronate in aggregating chains is present both in N-sulphated block regions and in regionsthat carry alternating N-acetyl- and N-sulphated glucosamine.